The Influence of the SIPD Application on Budget Management in the Makassar City Government, South Sulawesi Province - Mediaty Mediaty; Laode Abdul Dani Fakhri Rasyid; Ismah Muthiah; Saprudin Saprudin (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
In this study, the researcher studies the impact of the SIPD (Regional Government Information System) application on the performance of budget management at the Makassar City Government in South Sulawesi Province. In an explanatory research design with the approach based on quantitative methods, in this research the primary data was obtained with the help of structured questionnaires offered to 100 civil servants directly participating in the planning and financial departments involved in the SIPD-based budget process. The SPSS software was used in the multiple linear regression analysis of the relationships between three independent variables, which were system functionality, ease of use, and user satisfaction and the budget management variable as a dependent variable. The findings indicated that all the three indicators had a positive and significant impact on budget management. User satisfaction had the highest effect among them which shows that user experience is important in establishing the effectiveness of digital systems in governing citizens. The coefficient of determination (R 2) was 62.3 which implies that a large percentage of budget performance change owes its existence to the use of SIPD. The findings can indicate that once properly introduced and maintained, digital tools such as SIPD can become strategic enablers to improve the financial governance of the local level. This paper adds to the body of knowledge on e-governance because it addresses this gap on post implementation assessment on SIPD in large city municipalities.